2015
DOI: 10.1007/s00122-015-2587-9
|View full text |Cite
|
Sign up to set email alerts
|

Adult-plant resistance to Septoria tritici blotch in hexaploid spring wheat

Abstract: New QTL for Septoria tritici blotch detected in hexapoid spring wheat under field conditions across diverse environments. Septoria tritici blotch caused by the ascomycete fungus Zymoseptoria tritici presents a serious and consistent challenge to global wheat production. In particular the augmented use of soil management practices that leave large amounts of wheat stubble on the soil surface and global warming increases the chance of Septoria tritici blotch epidemics to emerge more frequently including in devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 44 publications
6
30
4
Order By: Relevance
“…Generally, qualitative resistance genes explain a large part of the variance, and this will also be reflected as high LOD scores (Raman & Singh, 2015). This also suggests that the chromosomal regions found in this study are quantitative resistance genes.…”
Section: Genomewide Association Analysissupporting
confidence: 62%
See 1 more Smart Citation
“…Generally, qualitative resistance genes explain a large part of the variance, and this will also be reflected as high LOD scores (Raman & Singh, 2015). This also suggests that the chromosomal regions found in this study are quantitative resistance genes.…”
Section: Genomewide Association Analysissupporting
confidence: 62%
“…As the GWAS resulted in relatively low LOD scores and R 2 values, the four QTL are most likely to be quantitative resistance genes. Additionally, earlier studies have identified STB resistance as a quantitative trait, rather than a qualitative (Dreisigacker, Wang, Cisneros, Jing, & Singh, ). This also suggests that the chromosomal regions found in this study are quantitative resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, alleles for the plant height and vernalization genes Rht-B1, Rht-D1, and Vrn-A1 were also determined, using Kompetitive allele specific PCR (KASP) assays (LGC Genomics applications note, http://www.kbioscience.co.uk/reagents/KASP_Taqmancomparison.pdf) described in Dreisigacker et al [25]. Additionally, some simple sequence repeat (SSR) markers were previously mapped in these two populations for studying Septoria tritici blotch resistance [26]. Markers with missing data points greater than 20% and segregation ratio beyond the range 0.5-2.0 were discarded from further analysis.…”
Section: Genotypingmentioning
confidence: 99%
“…More significant in wheat breeding is partial or quantitative resistance (QR), which is incomplete but generally effective against all genotypes of a pathogen, and is usually durable (Brown, ; Niks et al ., ). Numerous quantitative trait loci (QTLs) for QR to Septoria have been reported (reviewed by Brown et al ., ; see also Adhikari et al ., ; Dreisigacker et al ., ).…”
Section: Introductionmentioning
confidence: 97%